Effectiveness of Students’ Vocabulary Mastery Using the Comic “Donald Duck” in Junior High School - Marcell Ghangsar Putri; Fitri Yulianti; Tarcisia Sri Suwarti (Lingua Franca, 2023)
This research was focused on investigating the effectiveness of students' vocabulary mastery using the comic "Donald Duck" for 7th-grade students in SMP N 25 Semarang. This research aimed to compare the findings of students' vocabulary mastery before and after being taught Donald Duck comic media and to see if there was a significant difference in student achievement in their vocabulary mastery taught before and after using Donald Duck comic media. This research used a quasi-experimental design with two classes: experimental and control. This study's population consisted of 261 students in the seventh grade at SMP N 25 Semarang, and the sample consisted of 64 students from two classes, VIG and VID. Data was collected by giving a pre-test and a post-test and then analyzed in the SPSS program using the t-test formula. The analysis results show that students not taught to use comics have a "poor" ability, as seen from their post-test average score of 60.13. Students taught to use comics had "good" abilities, as seen from their post-test average score of 75.50. So, a t-test of 13,054 is obtained with a t-table of 2,042 at a significance level of 5%. It can be concluded that the t-test is higher than the t-table (13.054>2.042). This shows that there is a significant difference in vocabulary mastery between students who are taught using Donald Duck comics and those who are not taught using Donald Duck comics. This means the alternative hypothesis (Ha) is accepted, and the null hypothesis (Ho) is rejected. Learning vocabulary mastery using Donald Duck comics is effective.